Autoimmune pathogenesis of gestational diabetes mellitus: the risk of progression to type 1 diabetes mellitus - Skibińska, Milena; Kacerovsky, Marian; Grzesiak, Mariusz; Wujcicka, Wioletta Izabela (Frontiers in Endocrinology, 2025)
Gestational diabetes mellitus (GDM) is one of the most commonly diagnosed metabolic disorders in pregnancy, affecting between 5% and 20% of patients worldwide, depending on the diagnostic criteria and population. Although GDM pathogenesis is predominantly based on insulin resistance mechanisms resulting from the influence of pregnancy hormones, an increasing number of studies point to a significant role of immunological factors in the process of GDM development. In some GDM patients, autoantibodies targeting pancreatic beta cells are detected. Consequently, autoimmune processes may constitute an important element of GDM etiology, particularly in cases where GDM is a transitive condition leading to type 1 diabetes mellitus (T1DM) after the pregnancy. Disorders causing the destruction of beta cells within the pancreas precipitate permanent hyperglycemia in patients with autoimmune GDM (gestational diabetes mellitus with autoantibodies). characteristics. Genetic factors also play a significant role in this process, including single-nucleotide polymorphisms associated with the tissue compatibility system, such as HLA, CTLA-4, PTPN22 and IL2RA, which cause predisposition to T1DM. The following article discusses the current state of knowledge and presents GDM pathogenesis from the standpoint of immune mechanisms capable of affecting the development of this condition. It discusses potential markers that may help identify GDM patients at risk of progressing to permanent diabetes mellitus as well as possible diagnostic and therapeutic strategies based on the latest findings.